The radical, righteous and relevant Jesus in a coronavirus disease-defined world - Oliver, Willem H. (HTS teologiese studies, 2021)
Stephan Joubert has already made his mark in South Africa (and abroad) with his solid way of doing Theology. In this Festschrift, we wanted to accord recognition to him for what he has already made and for what he is currently doing with e-kerk. His book, Jesus Radical, Righteous, Relevant, having initially been written in Afrikaans, was translated in 2012 into English and depicts his heart for the followers of Jesus and the familia Dei, specifically in South Africa. This article is a journey through this book, with the current dilemma in our country and worldwide in the back of our minds, namely, the coronavirus disease (COVID-19) starting in 2019.Contribution: This article forms part of the Special Collection which will serve as a Festschrift for Prof Stephan Joubert to honour him for the tremendous work that he has done (and is still doing) in Theology in South Africa. I took his book, Jesus, Radical, Righteous, Relevant as basis and applied it to our current situation with COVID-19.